Lawrence Grossberg and Cultural Studies Today - Braga, Adriana (E-Compós, 2013)
Lawrence Grossberg is a scholar at the University of North Carolina (USA) and one of the most prominent exponents of American Cultural Studies, having worked with Stuart Hall, Richard Hoggart and James W. Carey. Author of Mediamaking: mass media and popular culture (with Charles Whitney and Ellen Wartella, Sage Publishers, 1998) and Caught in the Crossfire: Kids, Politics, and America’s Future (Paradigm Publishers, 2005), in June, 2013, professor Grossberg has been the Keynote Speaker of the 22nd Annual Meeting of Compós, in Salvador, Brazil. In this interview, Lawrence Grossberg speaks of his influences and of contemporary challenges for a cultural studies perspective. Keywords Cultural Studies. Communication Theory.